2008
DOI: 10.1002/ange.200801325
|View full text |Cite
|
Sign up to set email alerts
|

NO‐Dismutase‐Aktivität siebenfach koordinierter Mangan(II)‐ Komplexe von Pentaazamakrocyclen

Abstract: Redoxselektivität? Siebenfach koordinierte Mangan(II)‐Komplexe von Pentaazamakrocyclen fördern die NO‐Disproportionierung über einen neuartigen Dismutierungsmechanismus, der die Bildung labiler Metall‐Nitrosyl‐Addukte umfasst und mit dem MnII/MnIII‐Redoxzyklus verbunden ist (siehe Bild). Das metallgebundene NO zeigt in diesen Addukten die Reaktivität von NO− und NO+. Solche Superoxiddismutase‐Mimetika könnten in NO‐vermittelte Prozesse in biologischen Systemen eingreifen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…and ONOO − releases. This study thus demonstrates that the previously established in vitro chemistry of the SOD mimics used here5b is valid in vivo as well, thus leading to a rare example where in vitro chemistry explains very well in vivo effects.…”
Section: Methodssupporting
confidence: 62%
See 2 more Smart Citations
“…and ONOO − releases. This study thus demonstrates that the previously established in vitro chemistry of the SOD mimics used here5b is valid in vivo as well, thus leading to a rare example where in vitro chemistry explains very well in vivo effects.…”
Section: Methodssupporting
confidence: 62%
“…However, drawing an analogy with native enzyme,5a some of us have recently shown that such complexes do react with NO . , albeit at lower rates than with O 2 .− (the rate constant for aerobic reaction with NO was estimated to be 850 M −1 s −1 , whereas the catalytic rate constant for O 2 .− dismutation is 1×10 7 M −1 s −1 ) 5b. We proposed a new dismutation mechanism which involves the formation of labile metal–nitrosyl complexes and leads to the catalytic removal of large amounts of NO .…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…Besides removing superoxide, SOD mimetics may react with other ROS, which include hydrogen peroxide, peroxynitrite, carbonate radicals, peroxyl radicals, and alkoxyl radicals . SOD mimetics also react with reactive nitrogen species, which include nitric oxide . SOD mimetics, which generate additional hydrogen peroxide as a by‐product of the dismutation reaction, may decrease cell proliferation and enhance chemotherapy and radiotherapy treatment efficacy in cancer cells.…”
Section: Introductionmentioning
confidence: 99%